Implementation of the Murabahah Agreement in Financing Pension Funds at Bank Syariah Indonesia RFO Bandung - Seli Diana Putri; Muhammad Al Mighwar (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
Islamic banks are financial institutions that mediate the liquidity needs of society through various products and services. Islamic banking products are increasingly developing and competitive, including pension financing products, namely consumer financing which is only offered to retired workers (PNS, BUMN or BUMD) or retired widows. Pension financing is a low-risk type of financing. The evolution of BSI RFO Bandung pension fund customers has had its ups and downs. In this research, the problem is formulated how the pension financing mechanism is at BSI RFO Bandung and how is the implementation of the Murabahah contract in pension financing at BSI RFO Bandung. The purpose of this study is to describe the pension financing mechanism at BSI RFO Bandung and describe the application of a murabaha contract in pension financing at BSI RFO Bandung. bank, data checking/verification of data to obtain correctness of data completeness, field surveys with the 5C principle, evaluation of financing needs and decisions, execution of contracts and binding of collateral, and disbursement of financing. This study also found that the murabaha contract process for pension financing products is in accordance with the fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) No: 04/DSNMUI/IV/2000, concerning general provisions for murabahah financing and several provisions related to implementation and standard SOPs. murabahah financing by the Financial Services Authority.